Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
b: \(=x\left(x^4-y^4\right)+y\left(x^4-y^4\right)\)
\(=\left(x+y\right)\left(x^4-y^4\right)\)
\(=\left(x+y\right)\left(x^2-y^2\right)\left(x^2+y^2\right)\)
\(=\left(x^2+y^2\right)\left(x+y\right)^2\cdot\left(x-y\right)\)
b,(xy+4)2-4(x+y)2
=(xy+4)2-(2(x+y))2
=(xy+4)2-(2x+2y)^2
=(xy+4-2x-2y)(xy+4+2x+2y)
2) \(x^4y+xy^4=xy\left(x^3+y^3\right)\)
4) \(x^4+x^2+1=\left(x^2+x+1\right)\left(x^2-x+1\right)\)
a) x4 + x2 - 27x - 9
= (x4 - 27x) + x2 - 9
= x(x3 - 27) + (x - 3)(x + 3)
= x(x - 3)(x2 + 3x + 9) + (x - 3)(x + 3)
= (x - 3)(x3 + 3x2 + 9x + x + 3)
= (x - 3)(x3 + 3x2 + 10x + 3)
b) x2 - xy - x + y
= x(x - y) - (x - y)
= (x - 1)(x - y)
c) xy + 4 - x2 + 2y
= (xy + 2y) - (x2 - 4)
= y(x + 2) - (x - 2)(x + 2)
= (x + 2)(y - x + 2)
d) xy + y - 2(x + 1)
= y(x + 1) - 2(x + 1)
= (y - 2)(x + 1)
a,x4-4x3+8x2-16x+16
=(x4-4x3+4x2)+(4x2-16x+16)
=(x^2-2x)^2+(2x-4)^2
=x^2(x-2)^2+4(x-2)^2
=(x-2)^2(x^2+4)
x^2 + 3xy+2y^2 = x^2 +2xy+y^2+xy+y^2=(x+y)^2 + y(x+y)=(x+y)(x+2y)
x6+3x4y2-8x3y3+3x2y4+y6= x6+3x4y2+3x2y4+y6-8x3y3=(x2+y2)3-(2xy)3
= (x2+y2-2xy)[(x2+y2)2+2xy(x2+y2)+(2xy)2]= (x-y)2(x4+6x2y2+y4+2x3y+2xy3)
(x2+y2-5)2-4x2y2-16xy-16=(x2+y2-5)2-(4x2y2+16xy+16)=(x2+y2-5)2-(2xy+4)2
=(x2+y2-5+2xy+4)(x2+y2-5-2xy-4)=(x2+2xy+y2-1)(x2-2xy+y2-9)=[(x+y)2-1][(x-y)2-32]=(x+y-1)(x+y+1)(x-y-3)(x-y+3)
x4+324=x4+36x2+324-36x2=(x2+18)2-(6x)2=(x2+18-6x)(x2+18+6x)